Tumor-Infiltrating Myeloid Cells Co-Express TREM1 and TREM2 and Elevated TREM-1 Associates With Disease Progression in Renal Cell Carcinoma - Ford, Jill W.; Gonzalez-Cotto, Marieli; MacFarlane, Alexander W.; Peri, Suraj; Howard, O. M. Zack; Subleski, Jeffrey J.; Ruth, Karen J.; Haseebuddin, Mohammed; Al-Saleem, Tahseen; Yang, Youfeng; Rayman, Pat; Rini, Brian; et al. (Frontiers in Oncology, 2022)
Myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM) contribute to cancer-related inflammation and tumor progression. While several myeloid molecules have been ascribed a regulatory function in these processes, the Triggering Receptors Expressed on Myeloid cells (TREMs) have emerged as potent modulators of the innate immune response. While various TREM’s amplify inflammation, others dampen it and are emerging as important players in modulating tumor progression. For instance, soluble TREM-1 (sTREM-1) is detected during inflammation associates with disease progression while TREM-2 expression is associated with tumor-promoting macrophages. We hypothesized that TREM-1 and TREM-2 might be co-expressed on tumor-infiltrating myeloid cells and that elevated sTREM-1 associates with disease outcomes thus representing a possibility for mutual modulation in cancer. Using the 4T1 breast cancer model, we found TREM-1 and TREM-2 expression on MDSC and TAM and that sTREM-1 was elevated in tumor bearing mice in multiple models and correlated with tumor volume. While TREM-1 engagement enhanced TNF, a TREM-2 ligand was detected on MDSC and TAM, suggesting both TREM could be functional in the tumor setting. Similarly, we detected TREM-1 and Trem2 expression in myeloid cells in the RENCA model of renal cell carcinoma (RCC). We confirmed these findings in human disease by demonstrating expression of TREM-1 on tumor-infiltrating myeloid cells from patients with RCC and finding that sTREM-1 was increased in patients with RCC. Finally, TCGA analysis shows that TREM1 expression in tumors correlates with poor outcomes in RCC. Taken together our data suggest that manipulation of the TREM-1/TREM-2 balance in tumors may be a novel means to modulate tumor-infiltrating myeloid cell phenotype and function.